Scatter-hoarding rodents are better pilferers than larder-hoarders. (July 2018) - Wang, Zhenyu; Wang, Bo; Yi, Xianfeng; Yan, Chuan; Cao, Lin; Zhang, Zhibin
Abstract : Food hoarding is critical to rodents for their survival and reproduction. However, the seeds cached by rodents often suffer heavy pilferage by competitors. Therefore, compensation for cache loss is crucial, especially for scatter-hoarding rodents, as they cannot aggressively defend their stored seeds, whereas larder-hoarding rodents can. Pilfering caches of other individuals may be an effective way to compensate for cache loss for rodents. Hence, cache pilfering is likely to be as important as hoarding to food-hoarding rodents. Scatter-hoarding rodents may rely on their olfactory abilities and explore a wide area to retrieve their cached seeds, which may help to increase the probability of encountering and pilfering others' caches, whereas it is not essential for larder-hoarding rodents. We hypothesized that rodents that showed stronger scatter-hoarding behaviour would be better pilferers. To test this hypothesis, we investigated the relationship between scatter-hoarding and pilferage behaviours among four coexisting species of rodents using seminatural enclosure experiments in southwest China. Both hoarding and cache pilfering differed significantly between the four species. The predominant scatter-hoarding rodents, red spiny rats, Maxomys surifer, had a strong cache-pilfering behaviour, whereas yellow-bellied rats, Rattus flavipectus, mainly adopted larder-hoarding strategies and had a weak cache-pilfering behaviour. Chinese white-bellied rats, Niviventer confucianus, and chestnut rats, Niviventer fulvescens, had moderate scatter-hoarding and cache-pilfering behaviours. The intensity of cache pilfering was negatively correlated with the intensity of larder hoarding, but positively correlated with the intensity of scatter hoarding among the coexisting food-hoarding rodents. Our study suggests that the positive correlation between the intensities of scatter hoarding and cache pilfering is likely to facilitate reciprocal pilferage among scatter-hoarding rodents, which helps to maintain the stability of scatter-hoarding behaviour in these populations. Highlights: Hoarding and cache-pilfering behaviours differed between sympatric rodents. Scatter-hoarding intensity was positively correlated with cache-pilfering intensity. Larder-hoarding intensity was negatively correlated with cache-pilfering intensity. These correlations facilitate the stability of hoarding behaviour in the populations.